Pemilihan Metode Spin Off Unit Bisnis Syariah Dengan Pendekatan Analisa Faktor (Studi Kasus PT. BNI Syariah dan PT. Bank Syariah BRI) - Amzul Rifin; Imam T Saptono; H R Dewati (AL-MUZARA'AH, 2015)
The banking sector in Indonesia is classified as a competitive economic sector. That condition force the bank management to implement appropriate strategies and innovation to improve the capability of the company and the quality of services offered. Of the various strategies available, spin-off considered as one of the strategies that are quite popular among banking companies. The implementation of spin-off in Sharia Business Unit (UUS) in Indonesia is carried out with the different method among Commercial Bank (BUK). The research focuses on 2 (two) alternative spin-off methods, which is spin-off through existing bodies and through the establishment of a new entity, with a case study of PT. Bank BRI Syariah and PT. Bank BNI Syariah. The data collection process in this paper is will be done through 2 stages. The first step is using factor analysis method to assign factors that are considered significant in spin-off process, and the second step to determine the factors that are more considered for different methods by using pairwise comparison method. The results show that there are 6 (six) factors considered in spin-off implementation, and there are differences in the factor that considered in spin-off implementation between Islamic Banks that was formed through existing bodies and through the establishment of a new entity.